Brujería capitalista y turistas pishtaco: Tensiones ocultas en torno al turismo de ayahuasca entre los shipibo de San Francisco (Amazonia peruana) - Slaghenauffi, Doriane Sabine (2025)
The emergence of “shamanic tourism” in some Shipibo-Konibo villages and urban areas has led to a recrudescence of vernacular witchcraft practices, now integrated into the new sociological context of the commercialization of local vegetalist shamanism. This has brought about sorcery attacks both on rival shamans and on tourists seeking a shamanic and hallucinogenic experience, some of whom in turn become the target of sorcery rumors. These occult practices and interpretations can be seen, on the one hand, as forms of resilience adopted by Shipibo shamans in order to cope with and benefit from the current context of transition to capitalism, which is increasingly present within the communities, and, on the other hand, as manifestations of frustration and anxiety about the recuperation of local shamanism by global culture, symptomatic of the traditionally ambiguous links between gringos and Native Amazonians.